Project Management For Robocon 2005 - Mohamed, Abdul Rahman (Universiti Sains Malaysia, 2005)
Robocon 2005 is the project that participated by many of university and college not only from this country but all also all over the world. Other than that we, Science University of Malaysia allowed their students also took this challenge to held the name of university into that tournament. Many of them from the Mechanic Engineering School. The scope of this project is project management to planning, scheduling and also controlling the activity of the project. These projects also provide the alternative of problem solutions to improve the capability of the team. Until this day only 80 percents from the project has completed but the tournament has begin on April 2005.